Cultural criticism as an imperative for Christians - Aarde, Andries van (HTS teologiese studies, 2005)
In this article cultural criticism is approached from an epistemological perspective, in other words from the viewpoint of a theory of knowledge that includes matters such as the nature of knowledge, its sources, criteria, possibilities, and limits. Seen from this perspective, cultural criticism represents a critical position towards those culturally oriented studies, which advocate a positivist schema in epistemology. A cultural-critical disposition in Christian theology is to question whether meaningful life depends on a Christian’s acceptance and conformity to the so-called “orders of creation” as divine imperatives. Since such compliance was biblically legitimated as God’s will and wisdom, cultural criticism seeks for another theological validation that can create space for an “alternative wisdom” within a postmodern paradigm. The article aims at showing that dialectical thinking paved the way for applying critical theory in the humanities, theology and biblical exegesis. In the article different critical theories in firstcontinental (Euro-centric) philosophy and Christian theology are discussed. It argues that cultural criticism should be seen as an imperative for Christians because they ought to build their lives on the “cultural wisdom” of Jesus of Nazareth, which pertains to a “cultural-critical” position in his time.